Pharmacophore model generation & ligand based 3d-qsar Study and design of novel biphenyl derivatives of Benzimidazole as anti-mycobacterial agents - SAZID ALI; MOHD SHAHARYAR; SHAILENDRA SHARMA (International Journal of Pharma and Bio Sciences, 2017)
With the aim of designing new chemical entities with enhanced inhibitory potencies against Mycobacterium tuberculosis, the 3D-QSAR studies were carried out on biphenyl analogues of the tuberculosis drug, (6S)-2-nitro-6-[4-trifluoromethoxy)benzyl]oxy-6, 7-dihydro-5H-imidazo[2,1-b][1,3]oxazine (PA-824), as presented here. The 3D-QSAR studies involve analysis of the quantitative relationship between the biological activity of a set of compounds and their three-dimensional structural properties, using statistical correlation methods. Anti-mycobacterial activity (MABA) was considered for the 3D-QSAR studies using the pharmacophore modelling. The hypothesis model results were found statistically significant (q2 >0.7 and r2>0.8). Based on the findings of the 3D-QSAR model and structural insights, a series of new biphenyl derivatives of benzimidazole were designed and the anti-mycobacterial activities of the designed compounds were predicted. The analysis of pharmacophore generated has provided many clues about the structural requirement for the observed biological activity which shows that the electron-withdrawing groups at the terminal aryl rings are favorable for MABA inhibitory activity i.e., the addition of electron-withdrawing groups at this site will lead to increased MABA inhibition To add further, the OH, NH2 and CONH2Ph groups should be avoided at para position and lipophilicity is significant factor for further improvement.